Antecedent of service innovation effectiveness in small and medium enterprises: a case of hospitality sector in Nepal - Biswakarma, Gangaram; Gnawali, Achyut; Khatri, Bharat (International Journal of Operational Research/Nepal, 2020)
For a country’s economic growth and the productivity of the market, innovation is an integral factor. Service innovations today are transforming into a huge area for investigating dynamic relationships among technological and human processes that lead to the transition to the organization and management of services. In the hospitality industry, service innovation is very commonly needed. Conventional techniques in the hospitality industry are also very popular and notions prevails that hospitality is hard to innovate. With this the aim of this research is to examine the service innovation practices and its effectiveness in hospitality sector small and medium enterprises of Nepal. A sample of 308 responses has been collected from SMEs in hospitality sector. The findings indicate that the effectiveness of service innovation is limited. The highest correlation is observed with process innovation and followed by service innovation, organisational innovation, marketing innovation and human capital competency. It was found that there is an influence of service innovation, process innovation, marketing innovation, organizational innovation, and human capital competency on effectiveness of service innovation in SMEs of hospitality sector. SMEs from the hospitality sector could use innovation drivers to meet the ultimate company goals by service innovation effectiveness.